Impacts of budgeting on cost control and profitability of manufacturing firms in embu - MURITHI, DENIS WACHIRA (UoEm, 2024)
This study named impacts of budgeting on cost cost control and profitability of manufacturing firms in embu intends to establish the effects of budgeting on the financial performance and costs management of manufacturing firms located in Embu.The specific objectives of the study includes;(i)Forecast the financial flows.A budget is vital for businesses that are expanding quickly ,experience seasonal sales or have erratic sales trend and these firms always experience difficulties as a result of their inability to accurately predict how much sales they are likely to make in the near future.(ii)efficiently allocate resources.firms use budgeting as a tool to choose how much money or resources to allocate togiven task such as buying fixed asset or pay dividends.(iii)To measure performance.Making a budget with the intention of using it as the benchmark for evaluating financial performance is a typical goal since the firm will be able to take necessary actions on the gaps between actual performance and budgeted performance.The methodology I am intending to use while doing the research will include open minded surveys with a set of predetermined set questions which i will distribute to my samples,case studies so as to generate anin depth understanding of complex issues in my samples and interviews where am planning to arrage one on one meetings with my samples so as to mine answers to my questions.The benefits of this study includes creating financial stability for manufacturing firms by tracking costs and following a plan which will lead to profitability at the end